Learning and Thriving With Questions: a Helpful Resource for Teacher Researchers - Catherine Compton-Lilly (Networks: An Online Journal for Teacher Research, 2003)
Contemporary educators live is an era of advertised "quick fixes and simple solutions that too often leave us feeling cheated and alone. The acclaimed phonics program, the scripted behavior reinforcement scheme, and the carefully sequenced, research-based scope and sequence all leave us much as they found us - continuing to seek ways to improve instruction for our students. As teacher researchers recognize, no one resource will serve all of our needs and challenges. Collaboration from supportive peers is integral to developing and maintaining exciting, compelling, and productive research projects. However, there are resources that can support us as we embark on and continue this journey. Living the Questions: A Guide for Teacher Researchers is one of these resources.